Physical demands and performance indicators in male professional cyclists during a grand tour: WorldTour versus ProTeam category - Muriel, X.; Valenzuela, P. L.; Mateo-March, M.; Pallarés, J. G.; Lucia, A.; Barranco-Gil, D. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To compare the physical demands and performance indicators of male professional cyclists of 2 different categories (Union Cycliste Internationale WorldTour [WT] and ProTeam [PT]) during a cycling grand tour.